On Trigonometric Fourier Series Multipliers in λp,q Spaces - Tleukhanova, Nazerke; Bakhyt, Amangul (Eurasian Mathematical Journal, 2021)
In this paper, we investigate the problem of trigonometric multipliers in the sequence spaces λp,q. Embedding theorems of the Lorentz and Besov spaces into the space of trigonometric Fourier series multipliers are formulated.